Hadith #4257 - Sunan Abi Dawud - al-Qasim bin Ghzwan القاسم بن غزوان; Amr bin 'Uthman عمرو بن عثمان بن عفان; ibn Mas'ud; ibn Umar; Ishaq bin Rashid al-Juzri إسحاق بن راشد الجزري; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب; Shhab bin Khrash bin Hwshb شهاب بن خراش بن حوشب; Uthman ibn 'Affaan (Sunan Abi Dawud)
I asked: Messenger of Allah! tell me if someone enters my house and extends his hands to kill me (what should I do?) The Messenger of Allah (ﷺ) replied: Be like the two sons of Adam. The narrator Yazid (ibn Khalid) then recited the verse: “If thou dost stretch they hand against me to slay me.”
Grade: Sahih